Factors Affecting Natural Resources and Environment Development Salaya Subdistrict, Phutthamonthon District Nakhon Pathom Province - Srimauang, Suwin; Pruekpiti, Tewit (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were: 1. To study the level of factors affecting the development of natural resources and environment in Salaya Subdistrict, Phutthamonthon District. Nakhon Pathom Province and 2. To study guidelines for natural resource and environmental development in Salaya Subdistrict, Phutthamonthon District Nakhon Pathom Province Survey research used a questionnaire with a sample of 370 people, statistics used percentage, mean, standard deviation, t-test and descriptive statistics. The research findings were as follows: 1. Study the level of factors affecting the development of natural resources and the environment in Salaya Subdistrict, Phutthamonthon District. Nakhon Pathom Province Factors most affecting development in females (52.26) Marital status (27.73) Monthly income between 9,001-12,000 baht (22.13) Age range 18-30 years old (21.33) Self-employed (19.47) Secondary education (18.67). 2. Study the approaches for natural resource and environmental development in Salaya Sub-district, Phutthamonthon District. Nakhon Pathom Province preservation of public space ( = 4.011), community development activities ( = 4.07), public utilization ( = 3.85), environmental pollution ( = 3.081), participation of The people ( = 3.56)) interviewed 10 community leaders. Descriptive analysis. Guidelines for local organizations should be formulated as budgeting policies and activities for continuous natural resource and environmental development.